The Relationship between Banking Credit and Poverty Levels in Indonesia - Danang Adi Surya; Setyowati, Eni (Universitas Muhammadiyah Pontianak, 2026)
The banking sector plays a strategic role in Indonesia’s economy, acting as a financial intermediary and driver of poverty reduction. This study examines the relationship between bank credit and poverty levels in both urban and rural areas across Indonesia. Using a descriptive-quantitative method and Spearman Rank Correlation on 2000–2023 BPS data, the findings show a significant negative correlation between bank credit and poverty (Sig. 0.00) in all areas. These results highlight bank credit as a key factor in poverty alleviation, underscoring the need to expand public access to financial services.